2021
DOI: 10.1152/ajplung.00122.2021
|View full text |Cite
|
Sign up to set email alerts
|

Passive siRNA transfection method for gene knockdown in air-liquid interface airway epithelial cell cultures

Abstract: Differentiation of human bronchial epithelial cells (HBEs) in air-liquid interface (ALI) cultures recapitulates organotypic modeling of the in vivo environment. Although ALI cultures are invaluable for studying the respiratory epithelial barrier, loss-of-function studies are limited by potentially cytotoxic reagents in classical transfection methods, the length of the differentiation protocol, and the number of primary epithelial cell passages. Here, we present the efficacy and utility of a simple method for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…This occurs via endothelial nitric oxide synthase (eNOS) localized to the base of the cilia. Confirming this, we used a published siRNA protocol for primary ALIs ( 86 ) and found that eNOS siRNA but not nNOS siRNA reduced T2R Ca 2+ responses ( Figure 3A ). We also noted that, despite nearly identical Ca 2+ responses, F508del/F508del CF ALI cultures produced less NO in response to T2R agonists PTC, 3oxoC12HSL, quinine, apigenin, and DPD ( Figures 3B–F ).…”
Section: Resultssupporting
confidence: 59%
“…This occurs via endothelial nitric oxide synthase (eNOS) localized to the base of the cilia. Confirming this, we used a published siRNA protocol for primary ALIs ( 86 ) and found that eNOS siRNA but not nNOS siRNA reduced T2R Ca 2+ responses ( Figure 3A ). We also noted that, despite nearly identical Ca 2+ responses, F508del/F508del CF ALI cultures produced less NO in response to T2R agonists PTC, 3oxoC12HSL, quinine, apigenin, and DPD ( Figures 3B–F ).…”
Section: Resultssupporting
confidence: 59%
“…This occurs via endothelial nitric oxide synthase (eNOS) localized to the base of the cilia. Confirming this, we used a published siRNA protocol for primary ALIs (83) and found that eNOS siRNA but not nNOS siRNA reduced T2R Ca 2+ responses ( Fig 3A ). We also noted that, despite nearly identical Ca 2+ responses, F508del/F508del CF ALI cultures produced less NO in response to T2R agonists PTC, 3oxoC12HSL, quinine, apigenin, and DPD ( Fig 3B-F ).…”
Section: Resultssupporting
confidence: 60%
“…SiRNA transfection was performed on cells cultured submerged or cultured with ALI method as previously described with minor modified (5,(59)(60)(61). When BEAS-2B cells or submerged cultured HNECs reached 80% confluence, the cells were transfected with siMEX3B (100 nM, Thermo Fisher Scientific Company, Waltham, MA, USA), siTGFBR1 (100 nM, Viewsolid Biotech, Beijing, China), siTGFBR2 (100 nM, Viewsolid Biotech), siTGFBR3 (100 nM, Viewsolid Biotech), or the corresponding negative control siRNA (siNC, 100 nM) using Lipofectamine RNAimax (InvitroGen) for 8 hours according to the manufacturer's instructions.…”
Section: Cell Culture Stimulation and Transfectionmentioning
confidence: 99%